PERTANGGUNGJAWABAN PIDANA PELAKU YANG TURUT SERTA (DEELNEMING) DALAM TINDAK PIDANA TERORISME (ANALISIS PUTUSAN NOMOR: 792/PID.SUS/2019/PN JKT.BRT) - Agustino, Bartolomeus; Sari, Indah (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Terrorism is a frightening specter, the threat of punishment is not only for perpetrators of terror but perpetrators who participate in helping terrorism will be threatened with punishment. Therefore, it is very interesting and important to study further regarding how the criminal acts of participating (deelneming) in criminal acts of terrorism are regulated? and what is the criminal responsibility of perpetrators who participate in criminal acts in the analysis of the West Jakarta decision Number 792/Pid.Sus/2019/PN Jkt.Brt concerning the criminal act of financing terrorism? To answer this problem, a normative juridical legal research method is used with the approach method statutory and conceptual regulations. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that the regulations regarding the prevention of crimes of terrorism in Indonesia are based on Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism, and the regulations in Article 11 of Law Number 9 of 2013 concerning the Prevention and Eradication of Criminal Acts of Terrorism Funding. Criminal liability of perpetrators who participated (deelneming) in the West Jakarta Decision Number 792/Pid.Sus/2019/PN Jkt.Brt. The defendant's actions fulfilled all the elements of the second indictment, Article 4 in conjunction with Article 5 of Law Number 9 of 2013 concerning Prevention and Eradication of Terrorism Financing, and therefore the defendant was legally and convincingly proven to have assisted in providing funds, either directly or indirectly, by the intention is to be used in part to commit a criminal act of terrorism.